Scaling land and water technologies in Tanzania: Opportunities, challenges and policy implications - Mwongera, Caroline; Odhiambo Ageyo, Collins; Kimani, Peter (2020)
The scaling of land and water technologies has widely increased across different parts of the world; and is recognized as important for ecological systems. These technologies contribute to sustainable management of watersheds on which agriculture, food production and rural livelihoods for most developing communities depend upon. There are ongoing efforts designed to halt land degradation in the Western Usambara which have arisen from pressure on land resources mainly caused by demographic growth, deforestation and the abandoning of the traditional regenerative land use and farming systems.